2010
DOI: 10.1631/jzus.b0900250
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous contralateral testicular and bilateral adrenal metastasis of chromophobe renal cell carcinoma: a case report and review of the literature

Abstract: Chromophobe renal cell carcinoma (ChRCC) metastatic to the testis has not, to the best of our knowledge, been reported in the literature. Nor have there been reports of delayed bilateral adrenal metastasis of ChRCC. Here we report a case of metachronous contralateral testicular and bilateral adrenal metastasis of ChRCC in a 70-year-old man who underwent right radical nephrectomy for RCC six years ago. He was admitted to the hospital because of left intrascrotal enlargement of two-month duration. Ultrasonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…The time to metastasis generally occurs years beyond primary cancer presentation. In testicular metastasis, it usually occurs simultaneously or precedes the diagnosis of renal tumors [ 4 ]. We report a rare case of simultaneous presentation of RCC metastasis to the stomach, bladder, and ipsilateral left testicle 7 years after left nephrectomy for clear cell renal cell carcinoma (RCC).…”
Section: Introductionmentioning
confidence: 99%
“…The time to metastasis generally occurs years beyond primary cancer presentation. In testicular metastasis, it usually occurs simultaneously or precedes the diagnosis of renal tumors [ 4 ]. We report a rare case of simultaneous presentation of RCC metastasis to the stomach, bladder, and ipsilateral left testicle 7 years after left nephrectomy for clear cell renal cell carcinoma (RCC).…”
Section: Introductionmentioning
confidence: 99%
“…Bu tedavi ile operasyon sonrası ortaya çıkabilecek akut adrenal yetmezlik durumunun önüne geçilmiş olacaktır [13]. Biz hastamıza endokrinoloji önerisi ile operasyon önce-si, operasyon sırasında ve operasyon sonrası 20 mg intravenöz metil prednizolon tedavisi başlayıp daha sonra idame tedavisi uyguladık.…”
Section: Discussionunclassified
“…6 In our review of the literature, we identified 27 cases of metastatic RCC to the testes in the English language, and in all except for one, they were clear cell carcinomas. [5][6][7][8][9][10][11] In most cases, patients were between the sixth and seventh decade, 5,7-9 although in one publica- …”
Section: Discussionmentioning
confidence: 99%
“…Even in those having been previously treated for renal malignancy, disease relapse has present as recurrences in the testicle. 7 Thus, when evaluating an elderly patient with a testicular mass, the possibility of metastatic disease must be considered in the differential diagnosis, especially in the setting of suspected or remote malignancy.…”
Section: Marzouk Et Almentioning
confidence: 99%
See 1 more Smart Citation